A Framework for Interpreting Lateral Swelling Pressure in Unsaturated Expansive Soils. (3rd February 2021) - Li, Mingyu; Wei, Yanqing; Liu, Yunlong; Jin, Junwei
Abstract : Lateral swelling pressure (LSP) develops when expansive soil volume increment associated with water infiltration is restrained in a confined domain, for example, due to construction of civil infrastructure. In this paper, initially a flowchart is developed to highlight various key factors that influence the LSP mobilization according to lab and field studies collected from previous literature studies. Then extending unsaturated soil mechanics, a theoretical framework is proposed for illustrating the LSP mobilization in the field against retaining structures and pile foundations under different boundary conditions, respectively. An example problem for a basement wall and a pile foundation constructed in a typical expansive soil from Regina, Canada, is presented to illustrate the proposed theoretical framework. The framework and corresponding analysis presented in this paper can facilitate to provide rational designs of geotechnical infrastructures in expansive soils.